Heart and chest veins in the rabbit - E. Ümran Bozkurt; Nejdet Dursun (Eurasian Journal of Veterinary Sciences)
In this study, obtaining Gazi University, Department of Laboratory Animals 10 adult New Zealand rabbits(6 female, 4 male) were used as experimental animals. Colorized latex was injected to materials and materials were dissected and photographs were taken. It was observed in the rabbits used that there are two cranial caval veins: as the right cranial caval vein and the left cranial cava! vein. Great cardiac vein, middle cardiac vein, and right cardiac veins were determined to be the venous vessels of the heart. It was determined coronary sinus was found to be lacking in the rabbit. It was observed that right azygous vein was present in the rabbit and it was arosen from the right cranial caval vein.